Tissue-Resident Type 2 Innate Lymphoid Cells Arrest Alveolarization in Bronchopulmonary Dysplasia. (31st October 2020) - Mi, Lanlan; Zhu, Shaoxuan; Cai, Jiayu; Xu, Suqing; Xue, Zhengyang; Lu, Hongyan
Abstract : Bronchopulmonary dysplasia (BPD) is a severe complication of the respiratory system associated with preterm birth. Type 2 innate lymphoid cells (ILC2s) play a major role in tissue homeostasis, inflammation, and wound healing. However, the role in BPD remains unclear. The present study showed that ILC2s, interleukin-4 (IL-4), IL-13, and anti-inflammatory (M2) macrophages increased significantly in BPD mice as compared to the control mice. Administration with recombinant mouse IL-33 amplified the above phenomena and aggravated the alveolar structural disorder and functional injury in mice subjected to BPD, and the opposite was true with anti-ST2 antibody. In addition, the depletion of ILC2s in BPD mice with anti-CD90.2 antibody substantially abolished the destructive effect on BPD. In the treatment of BPD with dexamethasone, the number of ILC2s and M2 macrophages and levels of IL-4 and IL-13 decreased with remission as compared to the control group. This study identified a major destructive role of the ILC2s in BPD that could be attenuated as a therapeutic strategy.